GPS book tracker - Abd Razak, Nur Fitrah; Razali, Nurul Syafiqah Azmini; Mior Yusoff, Fatin Nurliyana; Daud, Mohd Shamsul (Universiti Teknologi MARA, Kedah, 2017)
Book tracker/book GPS is a tool or software which applies the same concept as RFID (Radio-frequency identification (RFID). Each year, the market value of RFID is rise and the library can’t effort to have it. Therefore, with some intervention with a minimum cost, book tracker has been developed. The GPS tracker can be affixed to an object/book used to track and manage Library Collections covering book, equipment, etc). Therefore, the library can prevent the existing problems in the Library such as reduce the number of missing books; locate the availability of the books and etc. This tool offers advantages in which the tracker can be read if just passed near a reader, even if it is covered by the object or not visible. The tracker can be detected even inside a case, carton, box or other container. Besides, this tool able to solve problems of missing books with a minimum cost.